Information and Software Technologies 19th International Conference, ICIST 2013, Kaunas, Lithuania, October 2013. Proceedings - Skersys, Tomas; Butleris, Rimantas; Butkiene, Rita.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 19th International Conference on Information and Software Technologies, ICIST 2013, held in Kaunas, Lithuania, in October 2013. The 34 papers presented were carefully reviewed and selected from 60 submissions. The papers focus on the following topics: information systems, business intelligence, software engineering, and IT applications.
Information systems -- Business intelligence -- Software engineering -- IT applications.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Information systems; Education; Computer Science; Software Engineering; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Computers and Education; Information Storage and Retrieval